2022
DOI: 10.1073/pnas.2120439119
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prolonged spaceflight on cerebrospinal fluid and perivascular spaces of astronauts and cosmonauts

Abstract: Long-duration spaceflight induces changes to the brain and cerebrospinal fluid compartments and visual acuity problems known as spaceflight-associated neuro-ocular syndrome (SANS). The clinical relevance of these changes and whether they equally affect crews of different space agencies remain unknown. We used MRI to analyze the alterations occurring in the perivascular spaces (PVS) in NASA and European Space Agency astronauts and Roscosmos cosmonauts after a 6-mo spaceflight on the International Space Station … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 26 publications
(34 reference statements)
1
61
1
Order By: Relevance
“…The mechanistic link between BMI and PVS is not known, but it is possibly related to higher intracranial pressure ( Barisano et al, 2021b ), as linear positive relationship exists between CSF pressure and BMI ( Berdahl et al, 2012 ), and/or to a reduced vascular contractility and vascular dysfunction, which is often found in obese people ( Stapleton et al, 2008 ). That intracranial pressure might influence the burden of MRI-visible PVS has also been argued by a recent study in astronauts and cosmonauts showing enlargement of MRI-visible PVS after long-duration spaceflight on the International Space Station ( Barisano et al, 2022 ), as prolonged spaceflight is associated with some radiological and clinical findings suggestive of high intracranial pressure, including pituitary gland deformity ( Kramer et al, 2020 ), ventricular enlargement ( Barisano et al, 2022 ; Jillings et al, 2020 ; Koppelmans et al, 2016 ; Kramer et al, 2020 ; Roberts et al, 2017 ; Van Ombergen et al, 2018 , 2019 ), optic disk edema and posterior flattening of the optic globe ( Mader et al, 2011 ). Further studies should investigate whether intracranial pressure affects the visibility of PVS on MRI and the flow of the PVS fluid, as it will provide a better understanding of the cerebrospinal fluid dynamics and clearance systems with important clinical implications for a number of neurological disorders.…”
Section: Neuroimaging Pvs In Humansmentioning
confidence: 66%
“…The mechanistic link between BMI and PVS is not known, but it is possibly related to higher intracranial pressure ( Barisano et al, 2021b ), as linear positive relationship exists between CSF pressure and BMI ( Berdahl et al, 2012 ), and/or to a reduced vascular contractility and vascular dysfunction, which is often found in obese people ( Stapleton et al, 2008 ). That intracranial pressure might influence the burden of MRI-visible PVS has also been argued by a recent study in astronauts and cosmonauts showing enlargement of MRI-visible PVS after long-duration spaceflight on the International Space Station ( Barisano et al, 2022 ), as prolonged spaceflight is associated with some radiological and clinical findings suggestive of high intracranial pressure, including pituitary gland deformity ( Kramer et al, 2020 ), ventricular enlargement ( Barisano et al, 2022 ; Jillings et al, 2020 ; Koppelmans et al, 2016 ; Kramer et al, 2020 ; Roberts et al, 2017 ; Van Ombergen et al, 2018 , 2019 ), optic disk edema and posterior flattening of the optic globe ( Mader et al, 2011 ). Further studies should investigate whether intracranial pressure affects the visibility of PVS on MRI and the flow of the PVS fluid, as it will provide a better understanding of the cerebrospinal fluid dynamics and clearance systems with important clinical implications for a number of neurological disorders.…”
Section: Neuroimaging Pvs In Humansmentioning
confidence: 66%
“… Hupfeld et al (2020) also showed greater increases in ventricular volume and free water (cranial fluid) shifts following 1 year in space compared to 6 months. A recent study on the perivascular space in the brain of NASA astronauts showed that shuttle crew had no significant increase after their mission whereas astronauts who spent 6 months in the ISS demonstrated significant perivascular space increase after flight ( Barisano et al, 2022 ). Further, Scott Kelly took significantly longer to re-adapt to Earth’s gravity environment after his 1-year ISS mission compared to his previous 6-month mission ( Kelly, 2017 ; Garrett-Bakelman et al, 2019 ).…”
Section: Level 1 Priority Recommendationsmentioning
confidence: 99%
“…However, another earlier study on perivascular space in a group of over 40 astronauts and cosmonauts, both novice and experienced fliers, showed that both groups developed significant increases in perivascular space after spaceflight. Interestingly, a significantly larger increase in the NASA astronauts was observed compared to Roscosmos cosmonauts ( Barisano et al, 2022 ).…”
Section: Level 1 Priority Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations